TOPOGRAPHICAL IMAGING OF ANTIGEN – ANTIBODY INTERACTION AND HEPTATIS B SURFACE ANTIGEN ON SELF ASSEMBLED MONOLAYER OF MICA - NAZEEMA BANU BASHEER; RAJASREE SHANMUGANATHAN; GNANAMBIGAI PALANICHAMY; TAMILMANI EEVERA; KUMARAN SHANMUGAM (International Journal of Pharma and Bio Sciences, 2014)
Patterning of antigen and antibody on a suitable substrate is essential for developing immunobiosensor and to study the immunocomplex formed by interaction of antigen and antibody on nitrocellulose membrane using Atomic force microscopy (AFM). The antigens were immobilized over nitrocellulose membrane and the immunoglobulins were allowed to react over the membrane containing the antigens. Analysis of the height histograms and the topography revealed the parameters such as size (24.61 to 63.61 nm) and molecular interaction between the antigens and antibodies. Heptatis surface antigen B (HBsAg) at an optimized concentration of 5 ng/ml (1:200 dilution) was successfully positioned on self assembled monolayer and its topography and surface were imaged.